2012
DOI: 10.1371/journal.pntd.0001799
|View full text |Cite
|
Sign up to set email alerts
|

The Interactive Roles of Aedes aegypti Super-Production and Human Density in Dengue Transmission

Abstract: Background A. aegypti production and human density may vary considerably in dengue endemic areas. Understanding how interactions between these factors influence the risk of transmission could improve the effectiveness of the allocation of vector control resources. To evaluate the combined impacts of variation in A. aegypti production and human density we integrated field data with simulation modeling.Methodology/Principal FindingsUsing data from seven censuses of A. aegypti pupae (2007–2009) and from demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 39 publications
(52 reference statements)
3
67
0
Order By: Relevance
“…Dengue outbreaks have occurred nearly every year in Taiwan since 1987, first appearing in the southern part of Taiwan, which has a high human population density. Dengue outbreaks usually increase during rapid urbanization, and a high human population density has been associated with dengue transmission because of its potential impact on human-mosquito contact [64, 65]. Our study results revealed that the clusters of Ae.…”
Section: Discussionmentioning
confidence: 73%
“…Dengue outbreaks have occurred nearly every year in Taiwan since 1987, first appearing in the southern part of Taiwan, which has a high human population density. Dengue outbreaks usually increase during rapid urbanization, and a high human population density has been associated with dengue transmission because of its potential impact on human-mosquito contact [64, 65]. Our study results revealed that the clusters of Ae.…”
Section: Discussionmentioning
confidence: 73%
“…A. aegypti thrives in urban environments in that the mosquito breeds preferentially in the artificial containers often used in urban water collection 2. The increased density of both mosquito and human populations, as part of urban population growth, compounds this effect in terms both of vector suitability and transmission of dengue 2,75. While current research and policy interventions often treat dengue expansion as a phenomenon associated with urban human settlement, the incidence of the disease in rural areas is also on the rise.…”
Section: Dengue In the Futurementioning
confidence: 99%
“…Adults disperse by flying typically short distances and may have difficulty navigating through urban landscapes (Harrington et al, 2005; Hemme et al, 2010; Scott et al, 2000a,b; Getis et al, 2003). Because of these features, patterns of human movement—especially in the large urban populations where dengue is prevalent—play a potentially large role in virus spread and persistence (Stoddard et al, 2009; Wen et al, 2012; Padmanabha et al, 2012; Teurlai et al, 2012; Mondini et al, 2009; Barmak et al, 2011; Vazquez-Prokopec et al, 2010). Variation in human movements patterns, however, are almost never incorporated in mathematical models of vector-borne diseases (Reiner et al, 2013).…”
Section: Introductionmentioning
confidence: 99%